Hemophagocytic lymphohistiocytosis as an etiology of bone marrow failure - Paolino, Jonathan; Berliner, Nancy; Degar, Barbara (Frontiers in Oncology, 2022)
Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of multiorgan system dysfunction that is caused by hypercytokinemia and persistent activation of cytotoxic T lymphocytes and macrophages. A nearly ubiquitous finding and a diagnostic criterion of HLH is the presence of cytopenias in ≥ 2 cell lines. The mechanism of cytopenias in HLH is multifactorial but appears to be predominantly driven by suppression of hematopoiesis by pro-inflammatory cytokines and, to some extent, by consumptive hemophagocytosis. Recognition of cytopenias as a manifestation of HLH is an important consideration for patients with bone marrow failure of unclear etiology.